Female Genital Warts: Global Trends and Treatments - Stanley A. Gall (Hindawi Limited, 2001)
The increasing incidence of human papillomavirus (HPV) infection and HPV-associated conditions such as genital warts in women is a global concern. Genital warts are a clinical manifestation of HPV types 6 and 11, and are estimated to affect 1% of sexually active adults aged between 15 and 49. HPV infection is also strongly associated with cervical cancer, and is prevalent in as many as 99% of cases. The psychological stress of having genital warts is often greater than the morbidity of the disease, and therefore successful treatment is crucial. Current treatments are patient-applied and provider-administered therapies. Imiquimod 5% cream, a patient-applied therapy, is an efficacious treatment with tolerable side-effects and a low recurrence rate, and has the potential to be an effective strategy for the management of genital warts.